Perceptions About Climate Change in the Brazilian Civil Defense Sector - Marchezini, Victor [UNESP]; Londe, Luciana Resende [UNESP]; Loose, Eloisa Beling; Saito, Silvia Midori; Marengo, José A. [UNESP] (Springer Nature, 2022)
Few studies have analyzed climate change perceptions in the disaster risk management sector. This research aimed to understand how civil defense experts are dealing with the climate change topic: what they learn and think about. An online survey was conducted between October and December 2021 with 1,063 participants from civil defense agencies in Brazil. The findings indicate: (1) most (80.6%) civil defense officers completely agreed that climate change will cause additional challenges to disaster risk management, while 10.1% stated that they are prepared to deal with it; (2) one quarter of the respondents (26.3%) completely agreed that they easily understand the information about climate change, but trust in the sources of information is a challenge—52.4% completely agreed and 40.5% partially agreed with information provided by scientists, but the levels of trust were reduced when referring to governments and press; and (3) about 30% of the respondents thought that civil defense work is associated with the Sustainable Development Goals (SDGs), despite SDGs 11 and 13 being related to disasters and climate change. The identification of civil defense’ perceptions on climate change is an important step in seeking pathways for increasing capacity building to achieve disaster risk reduction and climate change adaptation.
Keywords: Brazil; Capacity building; Disaster risk management; Emergency management; Risk governance; Risk perception